2008
DOI: 10.1080/20786204.2008.10873671
|View full text |Cite
|
Sign up to set email alerts
|

The practice of medicine at a district hospital emergency room: Middelburg Hospital, Mpumalanga Province

Abstract: Background: The aim of this study was to establish the type of clinical work done by the doctors in the emergency room at a district hospital in an underserved area. The findings of the study would assist the management in planning for training, recruitment and allocation of medical and nursing personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Within our study, 23% of diagnoses were categorised as trauma related, which is marginally lower than in other South African series, reported at between 23% and 48%. 4 , 5 , 7 It is, however, important to note that although trauma constituted the most common category at Zithulele, 78% of presentations are necessarily non-trauma related if a binary classification is used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within our study, 23% of diagnoses were categorised as trauma related, which is marginally lower than in other South African series, reported at between 23% and 48%. 4 , 5 , 7 It is, however, important to note that although trauma constituted the most common category at Zithulele, 78% of presentations are necessarily non-trauma related if a binary classification is used.…”
Section: Discussionmentioning
confidence: 99%
“…Patient load of on average 1334 patients per month was lower than other described patient loads in South African hospitals (a range of 1528 to 3399 patients per month). 4 , 5 , 7 This lower number of presenting patients may reflect issues with access or the presence of doctor outreaches to local clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover aging has been associated with depression of body immunity and is known to enhance susceptibility to infection [ 2 ]. The elderly subjects as compared with young and middle aged population are also highly susceptible to acute lower respiratory infection [ 4 , 9 ]. Dominici and colleagues in the year 2006 reported that short-term exposure to fine particle air pollution are dangerous, and significantly increases the risk for cardiovascular and respiratory disease among people over the age of 65 years [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most developing countries and resource poor nation adequate provisions of good medical are not widely available and the burdens of respiratory diseases are not well known. Some studies have been carried out in Nigeria and other African on pattern of medical cases admitted as an emergency, but none on the pattern of respiratory diseases presenting as an emergency among adult patients in sub-Saharan Africa [ 7 – 9 ]. This study was conducted to determine the pattern of respiratory diseases seen among adults in an emergency room (ER) and their mortality within twenty- four hours in a health facility in Nigeria.…”
Section: Introductionmentioning
confidence: 99%